Discretion of Fulfillment of Community Rights in Licensing Services in Sidoarjo Regency Environmental Government - Arif, Lukman; Hertati, Diana (Future Science, 2020)
The implementation of regional government affairs since decentralization politics is felt to be a big responsibility for the regions in creating welfare for their people. In the performance of functions that are the regions' responsibility, not all of them can be carried out by the Regent himself. Therefore, part of the Regent's authority duties, especially public service duties, need to be delegated to regional apparatus, one of which is the sub-district. The delegation of part of the Regent's authority to the sub-district head was administrative. The regional instrument in this sub-district was unable to provide optimal public services to the community. This condition's impact is that the community as citizens will not receive the benefits they are entitled to. This research is intended to look at the delegation of part of the Sidoarjo Regent's authority and the potential for the discretion of regional apparatus in the sub-district in administering public services. This research was conducted in Waru District and Sedati District, Sidoarjo Regency. Data collection was carried out using observation techniques and in-depth interviews (in-depth-interview) with key informants. The research results were analyzed qualitatively. The results of this study indicate that: a) The Head of District (Camat) discretion to exercise part of the Regent's authority in administering licensing services cannot be exercised. b) Implementation of licensing services runs as is; c) Community rights in obtaining service products are still stagnant.